Sosialisasi Kebersihan Lingkungan Aspek Penting dalam Peningkatan Kesehatan Warga di Perumahan Griya Punduan Permai - Wafizra, Ryokuji; Nurazizah, Naeila; Yanti, Olpy Nopy; Nurrahmah, Nurrahmah; Sobirin, Sobirin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Health and environmental cleanliness are two things that are interconnected and contribute to the quality of our life. A clean environment can prevent oneself and the environment from disease and keep the physical and mental well-being of residents. On the other hand, a polluted and dirty environment can be a source of disease, such as dengue fever, diarrhea, cholera, ARI (Acute Respiratory Infection), and many other diseases. This PKM aims to remind residents of the importance of environmental cleanliness on the quality of residents' health, as well as providing suggestions on actions that can be taken to improve environmental quality of environmental cleanliness and health. The PKM carried out found that poor waste management, lack of adequate sanitation facilities, and low public awareness of the importance of cleanliness had a significant impact on environmental health. Therefore, collaboration is needed between the government, citizen awareness, and private sector concern in creating a healthy environment, through educating the public, developing supporting infrastructure, and implementing policies that support sustainable environmental health.